Analisis Pengaruh Independensi dan Profesionalisme Dewan Pengawas Syariah terhadap Kinerja Bank Perkreditan Rakyat Syariah di Jawa Tengah - Prasetyoningrum, Ari Kristin (Jurnal Ilmu Ekonomi ASET, 2010)
Shariâa financial institution in Indonesia has shown fast development includingone of them is Bank Perkreditan Rakyat Syariâah (BPRS). Development of BPRS which is sofast brings concerns related to the purity of BPRS on shariâa principles so Dewan PengawasSyariâah (DPS) is formed. Realizing the importance of the role of DPS as a profession whichcan make public sure that service of BPRS followed by syariâa principles, so independenceand professionalism of DPS is needed in their duties. This research examined the effect ofeconomics and religious factor to the DPS independency so that effected the professionalismof DPS that would increase the performance of BPRS in Central Java. This research wasquantitative that describes the level of eksplanative causality variables. The data obtained byusing questionaire sent to all BPRS in Central Java. Measurement of variables using Likertscale, while an analysis tool used path analysis. Conclusion in this research is that economicsand religious factor have a significant effect on the independence of DPS on BPRS in CentralJava, DPS independency has a significant effect on professionalism of DPS with negativerelation, DPS professionalism doesnât significantly effect the Performance of BPRS and bothof DPS independency and DPS professionalism doesnât significantly effect the performance ofBPRS.Keywords: BPRS, Independency, Economics, religiousity, professionalism, and performance